Risk factors associated with tuberculosis at Mangaung Correctional Centre: retrospective analysis. - Mogoere, Serame (My University, 2014)
Background Prisons and jail systems worldwide are recognised as reservoirs for the transmission of communicable diseases. Tuberculosis (TB) is one of the fastest growing epidemics in prison populations in sub - Saharan Africa (SSA). Various factors have contributed to the breakdown of TB control in prisons in these low- and middle- income countries. Health care services in correctional centres are not adequately financed or supported, with little training offered to the health care professionals. TB is both preventable and curable. A range of evidence- based interventions exist to prevent, treat and mitigate exposure to the disease in the general population. High prevalence of TB in prison populations has been observed to be 10 to 35 times higher than the general population. Studies conducted in prisons world- wide show that TB cause significant morbidity and mortality among prisoners and prison staff. South Africa as a developing country has been one of the high burden countries in as far as Tuberculosis incidence is concerned. The TB epidemic has been worsened by the HIV/AIDS epidemic. An estimated 360 000 inmates move through the South African correctional centre system annually, this movement worsens the spread of communicable diseases especially TB. Correctional facilities house large numbers of inmates who are at high risk of developing TB because of their difficult life circumstances and risky behaviours. If the spread of TB in prisons is not properly dealt with and controlled, it may have serious repercussions for the public health in general. Mangaung Correctional centre is a privately administered prison situated in Bloemfontein. It is a maximum security facility with a population of 2928 male inmates. According to the TB registers, the prevalence of TB in this prison remains high. However factors associated with TB disease in this prison have not been studied. The objective of this study is to determine and evaluate the odds associated with the risk factors contributing to contracting TB among inmates at Mangaung Correctional centre during a study period of a year. Methods This was a retrospective case - control analytical study reviewing existing data from the medical records of inmates diagnosed and treated for TB disease between July 2009 and June 2010. The cases were identified from the TB registers and the controls which were grouped as non TB cases, were selected randomly from the records of inmates who were treated at each of the six housing unit clinics during the study period. A total of 1140 medical records were reviewed and relevant data was collected with a designed data capture sheet. The data was cleaned, checked for completeness and coded in Excel and then exported to STATA version 11.0, statistical software for appropriate analyses.The relationships between risk factors and TB were evaluated by univariate and bivariate analyses. Categorical variables comparison was described using Pearson chi- square test or Fisher’s exact test. A multiple logistic regression analysis was performed to find the association between TB disease and explanatory variables and odds ratios were calculated at 95% confidence interval and a p-value (p  0.05) was regarded as significant. Results Hundred (n = 100) inmates who were diagnosed and treated for TB were identified as TB cases and 1040 inmates with no history of TB were regarded as the control group (Non TB cases). The majority (42.6 %) of the inmates in this study population were aged between 31 -40 years. The mean age was 35.7 years, range 22 – 67 years. TB prevalence of 8.8% (n =100/1140) was found. The TB cases had more exposures than the non TB cases. 52% of inmates aged (31 - 40) years had TB disease. 47% of TB cases had low BMI  18.5 kg/m2 and 31% had previous history of TB disease. 58% of the cases were HIV positive and 34% had further compromised immunity with CD4 cell count  350 cells/mm3. 43% of TB cases were substance abusers. The differences between the TB and non TB cases were significant with p-values less than 0.05. The odds of contracting TB was not significant for the age group (31 – 40) years (OR: 1.02;95% CI: 0.64 – 1.62). HIV co – infection increased the odds of developing TB disease four times more (OR: 4.2; 95% CI: 2.64 – 7.00). Previous history of TB disease tripled the odds (OR: 3.58; 95% CI: 2.25 – 5.70) of contracting TB. Smoking was not found to increase the odds to develop TB and the odds doubled (OR: 2.1; 95% CI: 1.16 – 3.81) for ex – smokers.The odds of contracting TB were 1.8 times more for those inmates who used drugs. Length of stay in prison was not significantly associated with the risk of developing TB disease in this prison, p = 0.218. Conclusions TB prevalence of 8.8 % (8772 per 100 000) among inmates in this prison is nine times higher than that of the general population, (948 per 100 000) population. The high prevalence found in this prison confirms that TB disease among inmates is a serious health problem that cannot be ignored any longer. The study revealed that the odds of contracting TB are highly associated with the following risk factors: younger age group 21 – 30 years ,HIV co – infection, malnutrition (BMI  18.5),a history of previous diagnosed TB and substance abuse as compared to the control group. It is well documented that TB is the number one cause of death among HIV patients, and HIV co – infection increases the likelihood of reactivation, re – infection and progression of latent TB to active disease. Given the high odds associated with these risk factors, accurate and systematic interventions need to be developed and implemented immediately to control the development and transmission of TB and HIV in this high risk environment.